2023
DOI: 10.1093/cercor/bhad148
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age and sex on the absolute cell numbers of the human brain cerebral cortex

Abstract: The human cerebral cortex is one of the most evolved regions of the brain, responsible for most higher-order neural functions. Since nerve cells (together with synapses) are the processing units underlying cortical physiology and morphology, we studied how the human neocortex is composed regarding the number of cells as a function of sex and age. We used the isotropic fractionator for cell quantification of immunocytochemically labeled nuclei from the cerebral cortex donated by 43 cognitively healthy subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…Three studies conducted by different authors with a variable number of adult and aged individuals of both genders, using the (optical dissector) stereological and isotropic fractionator methods, showed that the cerebral cortex contains between 10-25, 14.7-32, and 7.2-14.4 billion neurons, respectively, the average number being 16.5, 21, and 10.2 billion, respectively. There was ample individual variation (100% or more) in all three studies, with no differences between males and females 6,13,14 , and no reduction in neuron numbers with age 6,14 . A neuronal loss of about 10% was reported by Pakkenberg and Gundersen 13 (Table 2), yet no histopathological study was made by these authors to exclude the presence of neurodegenerative diseases that could explain neuronal loss.…”
Section: Number Of Cerebral Cortex Neuronsmentioning
confidence: 80%
See 2 more Smart Citations
“…Three studies conducted by different authors with a variable number of adult and aged individuals of both genders, using the (optical dissector) stereological and isotropic fractionator methods, showed that the cerebral cortex contains between 10-25, 14.7-32, and 7.2-14.4 billion neurons, respectively, the average number being 16.5, 21, and 10.2 billion, respectively. There was ample individual variation (100% or more) in all three studies, with no differences between males and females 6,13,14 , and no reduction in neuron numbers with age 6,14 . A neuronal loss of about 10% was reported by Pakkenberg and Gundersen 13 (Table 2), yet no histopathological study was made by these authors to exclude the presence of neurodegenerative diseases that could explain neuronal loss.…”
Section: Number Of Cerebral Cortex Neuronsmentioning
confidence: 80%
“…Expansion of the cortical area of the brain, especially the neocortex, occurred in all mammals, although it was particularly more intense and faster in primates. This expansion was both in absolute terms and relative to the rest of the brain, causing the human brain to acquire more folds and grooves, with the gyri becoming more tortuous 14 , 49 , 50 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation